Being a Parent and not a Teacher: the Case of Specific Learning Disabilities - Padeliadou, Susana; Chideridou, Anastasia (International Journal about Parents in Education, 2023)
Living with a child with Specific Learning Disabilities (SLD) can be highly demanding or frustrating at times. In this paper we focus on the everyday reality and demands on the parents, their relationship with their children, and their reflection on these experiences. Through semi-structured focus-group interviews, we collected data from 15 parents (13 mothers and two fathers) in groups of 4-6 individuals. The two major questions around which the interviews were structured were 1) How did the child’s Specific Learning Disabilities impact on the everyday life of the family and especially of the parents? 2) What would they need and what would they do differently, if they could go back in time, to support their child? Based on the analyses of the interviews, three major issues were revealed: the high time-demands and therefore, lack of leisure-personal time, the lack of knowledge regarding SLD, and the retrospective regret and guilt of the parents. All parents appeared to struggle to balance between two, conflicting roles: the parent and the teacher roles. Lookingback, they strongly regrettedthepressure they had asserted on their children, often leading to verbal and even physical abuse.